2015
DOI: 10.1097/fch.0000000000000056
|View full text |Cite
|
Sign up to set email alerts
|

Using Community-Based Participatory Research to Identify Health Issues for Cambodian American Youth

Abstract: Lack of data disaggregated by ethnic group and the widespread perception of Asian Americans as "model minorities" often masks the health needs of specific groups within the Asian American population. Limited research focuses on health and psychological well-being among Cambodian American youth despite risk of negative educational and behavioral outcomes as well as high levels of trauma and psychiatric symptoms among first-generation Cambodian refugee adults. This article describes the development of a health s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…This is consistent with Filipino cultural values, given the importance of family-centeredness, respect for elders and cultural traits such as hiya (shame), pakikisama (smooth interpersonal relationships), and kapwa (togetherness) within the Filipino community. 36 Our results revealed that adolescents valued and providers promoted open discussion while parents and grandparents felt open discussion was a form of disrespect or talking back. This is consistent with a study by Chung et al in which “parents and grandparents felt that values were transmitted best through traditional Filipino respect for parents who often eschewed open discussion.” 22 The important role of parent-child communication and its effects on intergenerational relationships and family dynamics has been described among other Asian subgroups.…”
Section: Discussionmentioning
confidence: 70%
“…This is consistent with Filipino cultural values, given the importance of family-centeredness, respect for elders and cultural traits such as hiya (shame), pakikisama (smooth interpersonal relationships), and kapwa (togetherness) within the Filipino community. 36 Our results revealed that adolescents valued and providers promoted open discussion while parents and grandparents felt open discussion was a form of disrespect or talking back. This is consistent with a study by Chung et al in which “parents and grandparents felt that values were transmitted best through traditional Filipino respect for parents who often eschewed open discussion.” 22 The important role of parent-child communication and its effects on intergenerational relationships and family dynamics has been described among other Asian subgroups.…”
Section: Discussionmentioning
confidence: 70%
“…The data for this study come from a larger mixed methods study of Cambodian American adolescents that used a community‐based participatory research (CBPR) framework (Minkler, ). A more detailed discussion of procedures describing the development of the university–community partnership and community engagement is available elsewhere (Sangalang, Ngouy, & Lau, in press; Sangalang, Chen, Kulis, & Yabiku, in press).…”
Section: Methodsmentioning
confidence: 99%
“…Indicators of poor psychological and behavioral adjustment among the children of Southeast Asian refugees reflect the challenges these communities face, including high levels of depressive symptoms and low self-esteem (Portes and Rumbaut, 2001;Sangalang et al, 2015) and disproportionately high rates of delinquency (Go and Le, 2005;Spencer and Le, 2006). Intergenerational conflict rooted in cultural differences between parents and children has been associated with elevated risk of depression and behavioral problems among Southeast Asian youth (Choi et al, 2008;Ying and Han, 2007).…”
Section: Introductionmentioning
confidence: 99%